# Question: Evaluate Expression with 37’s

## Comment on Evaluate Expression with 37’s

### If I let a=37, then a^2-23a-a

If I let a=37, then a^2-23a-a-15a; I don't get the same answer, why? ### What answer are you getting

What answer are you getting when you evaluate the expression?

### Hi if i let x=37, I get the

Hi if i let x=37, I get the expression x^2 -23x - x - 15x
then, x^2 - 38x - x
then, x^2 - 39x
then, x(x-39)
which gives me 0 and 39 as possible values for x when I put the equation = 0

I chose 0 because its one of the answer choices. I know its wrong from the video but could you explain why. ### The small error you just made

The small error you just made is very common.

Once you saw got to the EXPRESSION x(x-39), you transformed it into the EQUATION x(x-39) = 0.

However, there is no such EQUATION.
We still need to find the VALUE of x(x-39) when x = 37

So, we must take x(x-39) and replace the x's with 37's
We get: 37(37-39)
Simplify to get: 37(-2)
Evaluate to get: -74

Does that help?

Cheers,
Brent

It did! ;)

### Could you factor out 37 after

Could you factor out 37 after you've turned 37^2 into (37)(37) and 37 into (37)(1)
I got the same answer, but is this just a coincidence? Or even if it's not a coincidence. Is there more room to make a mistake by factoring out 37 instead of the way you showed above. I hope that made sense. Thanks ### Great idea!

Great idea!
We can definitely evaluate the expression by first factoring out of the 37.
We get:
37² - (23)(37) - 37 - (37)(15) = (37)(37) - (23)(37) - 37 - (37)(15)
= 37(37 - 23 - 1 - 15)
= 37(37 - 23 - 1 - 15)
= 37(-2)
= -74

Cheers, Brent

Very Clear